Source of Information: between domination and threat to impoverish perspective of local public - Fadilah, Efi; Bajari, Atwar; Suryana, Asep; Hasan, Nik Norma Nik (University Libraries of the University of Nebraska--Lincoln, 2020)
The use of information sources in the information gathering process for news media content is very crucial in the context of its role and function as an instrument in building citizen literacy. However, in cases where the local news media is relatively highly dependent on local government, many critical issues arise. Essentially, the relationship is symbiotic, but in reality, local news media is more dependent on local government. The local government almost functions as the backbone of local news media through its multiple roles; as the source of information, the source of income, and the main market for local media. Through a case study, this article describes this relationship from the perspective of local news media and the point of view of local government, its manifestation in reporting, and the critical issues that must be considered. The research object was 4 local newspapers in West Sumatra Province, one of 34 provinces in Indonesia. The research data were obtained through interviews with newspaper editors and government public relations officials, content analysis, and literature review. The findings indicate that the power imbalance in the relationship causes the minimum voice of ordinary citizens in media coverage based on the usage pattern of local newspaper sources. Information sourced from government elements dominates the content of local newspapers, followed by information sources from local elites. Primarily, this practice impoverishes the public's perspective and makes the content of local newspapers less relevant, thereby widening the distance between the local newspapers and the local public.